Welfare policy under New Labour : Views from inside Westminster - Bochel, Hugh M. (Book collections on Project MUSE., 2007)
Welfare reform is a central part of the modernisation programme adopted by the Labour Government since 1997. This book examines the role of Parliament in the formulation and scrutiny of welfare policy, focusing in particular on how MPs and Peers view their influence on policy.